Structure and content of professional psychological competence of the future practicing psychologists of educational establishments - Панасенко, Е. А.; Кучков, В. С. (Scientific notes of the pedagogical department, 2018)
The article deals with the theoretical and methodological analysis of the issue that concerns the structure and content developing of the professional psychological competence of the future practicing psychologists of educational establishments. It is noted that the professional psychological competence of a practicing psychologist is a complex personal formation in the system of his professional activity, in which a specialist is capable of effectively interacting with people and performing psychological tasks and solving the problems that arise.The professional psychological competence of a practicing psychologist is presented as a structural combination of elements that are combined with each other as part of a unified general structure of the professional psychological competence of a practicing psychologist of an educational establishment.Social-perceptual competence is the practicing psychologist`s knowledge of the peculiarities of people`s mental development, the motives of their behavior, the peculiarities of their interactions and so on.Socio-psychological competence is the practicing psychologist`s knowledge of the psychological patterns of behavior, activities and relationships of people and the ability to apply them.Communicative competence is the ability of a practicing psychologist to establish and maintain the necessary contacts with children, their parents, and educators.Auto-reflective competence is a system of psychological knowledge and skills of the practicing psychologist that allows to carry out self-knowledge, self-control, self-examination, self-esteem.Healthcare-saving competence of a practicing psychologist is a complex integrative education of the personality-activity education, within which psychological and valeological knowledge, skills, abilities, psychological properties of the person integrate into the system-structural unit, ensuring the efficiency of both professional activities as well as the vital ones in general.Information technological competence of a practicing psychologist of an educational establishment is an integrative personal and activity characteristic of the specialist, which includes a set of knowledge, skills, abilities and activities, and subjective experience, cognitive and social motivation, individual and personality characteristics of a psychologist.Psychological pedagogical competence is considered by the scientists as a complex combination of social-perceptual, socio-psychological, communicative and auto-reflexive competencies, taking into account the value-orientation factors of the professional activity of a practicing psychologist of the educational establishment.Conflict-related competence is a system of psychological knowledge about the specifics of conflicts; the ability to analyze them, influence the participants of conflicts and resolve conflicts constructively.